Biocidal activity of plant-derived compounds against Phytophthora infestans: An alternative approach to late blight management. (December 2020) - Najdabbasi, Neda; Mirmajlessi, Seyed Mahyar; Dewitte, Kevin; Landschoot, Sofie; Mänd, Marika; Audenaert, Kris; Ameye, Maarten; Haesaert, Geert
Abstract: The current study aimed to evaluate the potential biocontrol capabilities of different essential oils (EOs) including juniper, tea tree, clove, thyme, cinnamon, turmeric, pepper and rosemary at application rates of 0.41, 0.83, 1.66, 3.33 and 6.66 μL mL −1 for control of Phytophthora infestans ; the causal agent of potato late blight in vivo and under greenhouse conditions. In particular we tested the highly pathogenic genotype, EU-13-A2. Plant extract Timbor® ( Thymus vulgaris -derived compound) was similarly applied as an alternative reference to the essential oils. The effectiveness of plant compounds was initially determined by measuring the effective dose (ED50 ) reducing P. infestans sporangial germination by 50%. Among the nine tested compounds, thyme and tea tree EOs showed the strongest inhibitory effect on sporangial germination, with ED50 values between 0.12 and 0.37 μL mL −1, compared to the fungicide control Ranman-top® (160 g L −1 Cyazofamide). Clove EO, thyme EO and Timbor® significantly inhibited P. infestans mycelial growth even at the lowest concentration tested (0.41 μL mL −1 ). Inhibitory effects of compounds were also assessed in response to late blight in vivo, and the results were then compared with greenhouse screening. In the detached-leaflet assay, pepper, rosemary EOs and Timbor® showed reduction of disease development at all concentrations except for 0.41 μL mL −1 . In dose–responses, rosemary, thyme EO and Timbor® were the most effective compounds in reducing late blight (more than 80% disease reduction) over time. Within a 35-day period, these compounds also resulted in the lowest level of disease severity in susceptible potato plants (cv. Bintje) when treated 12 h before inoculation, demonstrating their protective effect against late blight under greenhouse conditions. This study presents evidence for the potential use of commercial plant derived compounds as botanical fungicides against P. infestans to control infection on potato plants. Highlights: First study on anti-oomycidal activity of juniper, tea tree, pepper, clove and turmeric EOs against Phytophthora infestans . Considering rosemary, thyme, turmeric, tee tree EOs and Timbor® as effective compounds in reducing potato late blight. High conformity of detached-leaflet assay with whole-plant assay in dose-responses for Phytophthora blight assessments. Providing a baseline information on application of essential oils as botanical fungicide against late blight in the field.